Personal Value Systems of American Managers - England, George W. (Academy of Management Journal, 1967)
The personal value systems of 1072 American managers are studied for their contribution to the understanding of managers and their behavior. A theoretical model for analyzing the impact of values on behavior is presented and utilized. Major results are explored with respect to the impact of personal values systems on the behavior of managers.